تقوية عقدة جائز عمود طرفية باستخدام قضبان ربط قطرية ضمن العقدة مضافة في مرحلة التنفيذ - تريكية علي; سليمان وليد (Latakia University Journal -Engineering Sciences Series, 2019)
This study investigates the forces that affect the joints of the concrete frames and the tensile force generated inside it and the resulting cracks in the joint due to the lack of accidental Reinforcement . and Bibliographic Study about strengthening frame joints with diagonal bars added in carrying out stage include different positions to laying this bars with various diameters,and searching the possibility of using it with cfrp products to strengthening non effective joints after studying previous experimental studies, the analytical study of this research discuss non studied case of strengthening external beam column joint dont have horizontal strips using diagonal bars to reach at the end of research that the diagonal added bars strengthening the concrete connection and absorb diagonal stress inside the joint then good contributing in absorbing energy and delaying joint falling. يتناول البحث دراسة القوى المؤثرة على عقد الإطارات البيتونية وقوى الشد القطرية المتولدة فيها والتشققات الناتجة في العقدة بسبب القصور في التسليح العرضي. بالإضافة لدراسة مرجعية لطريقة تدعيم العقد البيتونية بقضبان ربط قطرية مضافة في مرحلة التنفيذ, وتشمل الدراسة المرجعية عدة طرق لتوضع هذه القضبان بأقطار مختلفة, مع إمكانية استخدامها بشكل مختلط مع مركبات الألياف الكربونية لتدعيم العقد البيتونية غير المحققة. بعد دراسة النتائج التجريبية للأبحاث السابقة, تتناول الدراسة التحليلية الخاصة بهذا البحث حالة غير واردة في الدراسة المرجعية, وهي تقوية عقدة جائز عمود طرفية مستوية غير مسلحة على القص باستخدام قضبان ربط قطرية لنصل بنتيجة البحث إلى فعالية إضافة القضبان القطرية في زيادة مقاومة العقدة بنسب جيدة وامتصاص إجهادات الشد القطرية في بيتون العقدة وبالتالي المساهمة في صرف الطاقة وتأخير انهيار العقدة.